Outcome of COVID-19 in children: results of a 12-month follow-up - T. M. Chernova; V. N. Timchenko; E. V. Barakina; A. A. Zherebtsova; N. S. Gusarova; Yu. S. Khabarova; V. V. Bulygina; D. E. Shakhrai; A. V. Zhiglova; E. A. Ttsvetkova (Журнал инфектологии, 2022)
At present, there are isolated data on the clinical outcomes of COVID-19 in children, especially those who have experienced asymptomatic and mild forms of infection.Purpose: to analyze the nature and frequency of postCOVID symptoms in children during 12 months. after recovery.Materials and methods. The influence of demographic indicators, premorbid background, severity of infection and therapy in the acute period of the disease on the nature and frequency of symptoms in 1079 children who underwent laboratory-confirmed COVID-19 was studied. The results are presented with proportions (%) and calculation of 95% confidence interval according to Klopper-Pearson. Differences between groups were assessed using Pearson’s chi-square test. Differences in the groups were considered statistically significant at p < 0,05.Results. Health disorders in the post-COVID period were observed in 8,5% of children, more often in school-children aged 7–17 years (68.4%). Concomitant conditions were found in 38,0%. In most cases, the consequences were noted after a mild form of COVID-19 (77.2%), however, 13,0% of patients experienced an asymptomatic form of infection. Among convalescents, changes in the emotional sphere (2,1%), headache (1,8%), symptoms of asthenia (1,6%), cardiovascular (1,5%), dyspeptic (1,3%) were more often observed, cognitive (1,3%) disorders, neurotic disorders (1,0%), less often respiratory (0.8%), endocrine (0,4%) and visual (0,4%) systems, musculoskeletal system were involved (0.2%). Girls were significantly more likely to have vegetative disorders, while boys were significantly more likely to suffer from cognitive functions. Various antiviral therapy options (interferon-alpha, an oral antiviral drug, or a combination thereof) in the acute period of COVID-19 did not affect the possibility of post-COVID disorders, but there was a tendency to increase the frequency in children who did not receive etiotropic treatment (control group). In 14.1% of cases, post-COVID symptoms appeared late – after 5–10 months. after recovery. The course of rehabilitation therapy, including drug treatment and non-drug methods, made it possible to quickly restore the state of health of the observed children.Conclusion. In most cases, the violations were of a functional nature, due to a disorder of autonomic regulation. Rehabilitation and dispensary observation programs will allow timely restoration of the quality of life of children who have had COVID-19, including in a mild and asymptomatic form.